Property Investment in Kurdistan (Iraqi Kurdistan): A Case Study of Kurdistan Region of Iraq, from 2003-2020 - Ali, Ranjdar Mustafa; Hamawandy, Nawzad Majeed; Qader, Abdulkhaleq Nader; Kakil, Raed Mohammed (The journal of contemporary issues in business and government, 2021)
The construction of housing in Kurdistan has changed the face of major cities throughout the region. Since 2003, sudden developments have seen ample structural components and massive housing projects that have transformed their towns' landscape. The increase in housing demand, a booming economy, economic growth rates in the region, relative safety in Kurdistan have fueled certain dimensions of Kurdistan's development, causing many people from nearby neighborhoods of Kurdistan to migrate into the region. This has required an increase in employment opportunities from housing projects' development and their ability to afford to house (Doski, 2015, p. 18). The number of foreign and local businesses recruiting from the current workers has been growing. The real estate boom that has engulfed Kurdistan since the independence of Iraq in 2003 has been one of the drivers of such economic development in Kurdistan. It can be anticipated that this growth will extend into the southern and central regions of Iraq once the security environment there is secure. Travel participation has also helped boost the Kurdistan's economic development. The road infrastructure has also been expanded and improved. New roads have been established, and Erbil International Airport will get a brand new terminal with one of the world's longest runways. In the country, 78 property developers amount to approximately $5.8 trillion, which is 42.9 percent of capital investment and 44.51 percent of investment property, allocated to date, making it the highest investment in capital and property in any field in the country (Hassan, 2017, p. 59). Since 2003, the favorable investment law has allowed this industry to thrive, the need for such housing developments is tremendous, and these houses provide 24-hour electricity, full gas, and irrigation systems as well as 24-hour protection, which is essential for companies working in Kurdistan to make these projects appealing both for residential purposes.